PENGEMBANGAN ANTARMUKA WEBSITE E-COMMERCE TOKO-TOPIA BERBASIS KOMPONEN MENGGUNAKAN REACTJS - Muhammad Rifki Syahada (CV. Adiba Aisha Amira, 2026)
This project aims to design and develop a responsive and interactive e-commerce website user interface (UI) named Toko-Topia using ReactJS. By utilizing this modern JavaScript library, the development focuses on performance, user experience (UX), and ease of navigation for customers. The developed website features functionalities such as product search, a shopping cart system, and API integration for checkouts, providing an optimal online shopping experience. This technology also enables efficient component management, supports real-time data updates, and enhances application scalability. The implementation of ReactJS in this e-commerce website development offers a modern solution for businesses to enhance their digital presence. The results of this project are expected to contribute to improving user experience in online shopping while supporting the growth of the digital economy in Indonesia.